2021
DOI: 10.4208/eajam.100520.040820
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of a Ternary System for Macromolecular Microsphere Composite Hydrogels

Abstract: In this paper, we study a ternary system for macromolecular microsphere composite (MMC) hydrogels. Assuming that the graft chains are distributed randomly around the macromolecular microspheres, a phase transition model was constructed. The stabilised-scalar auxiliary variable (S-SAV) approach is used to present a first-order energy stable scheme for solving the nonlinear system. Some numerical experiments are carried out to show the accuracy of the scheme, including the mass conservation of the volume fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Figure 6.8 displays the plot of the φ 2 variable at a sequence of time instants, t=0, 3.6, 6.52, 8, 10, 26, 85, 278 and 500, respectively. It is observed that the red area in the third row becomes larger, that is, the structure is tighter, which is consistent with [32,34].…”
Section: Numerical Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Figure 6.8 displays the plot of the φ 2 variable at a sequence of time instants, t=0, 3.6, 6.52, 8, 10, 26, 85, 278 and 500, respectively. It is observed that the red area in the third row becomes larger, that is, the structure is tighter, which is consistent with [32,34].…”
Section: Numerical Resultssupporting
confidence: 70%
“…In this section, we perform some numerical simulations using the proposed scheme (3.17). In [32], the authors simulated several numerical examples for solving three-component MMC-TDGL equations by the SAV method and showed some phase transition processes, with different initial concentrations as well as the statistical segment lengths a i , i = 1, 2, 3, consistent with an earlier work [34]. The statistical segment lengths a i in the deGennes interfacial gradient terms, 1 36 3 i=1 a 2 i φi |∇φ i | 2 , i = 1, 2, 3, determine the interface thickness.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAV method also keeps its shortcomings that is only the modified energy is unconditionally stable but not the original one. More applications can be found in previous studies [23][24][25][26], and the convergence and error analysis are presented in previous studies [27][28][29][30]. Other than the above approaches to establish the energy stability, time exponential time differencing (ETD) approach has also been reported in recent years to obtain higher order temporal accuracy with explicit treatment of nonlinear terms.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the IEQ and SAV approaches can be used to design linear and energy stable numerical schemes, which can improve the computational efficiency of many relatively complex problems [41,43,48,51,56,61], and have been rapidly developed in recent years. And also, the stabilization method turns out to be a useful tool to extend the above methods to a higher-order accuracy of time [28,29,48,58,59]. These numerical techniques possess two main features: mass conservation and energy dissipativity (conditionally/unconditionally).…”
Section: Introductionmentioning
confidence: 99%